A single center retrospective study of systemic reactions' distribution and risk factors to subcutaneous immunotherapy with dust mite extract in patients with allergic rhinitis and/ or asthma. Issue 1 (January 2023) - Zhang, Xude; Liu, Jingjing; Chen, Hui; Guo, Beibei; Liu, Fengxia; Wang, Xijuan
Abstract: Objective: To analyze various risk factors including causes that may lead to adverse reactions, especially systemic adverse reactions（SRs）, before and after mite allergen subcutaneous immunotherapy (SCIT), so as to provide real-world reference data for further improving the safety of mite allergen SCIT. Methods : The local adverse reactions（LRs）and SRs of 230 patients with allergic rhinitis and/or asthma who received SCIT in Weifang people's hospital were analyzed retrospectively. The data of patient characteristics, drug factors and environmental elements of adverse reactions were collected and statistically analyzed. Results : There were 28 cases (12.2%) of SRs in 230 patients. All the patients received a total of 7515 injections and 37 SRs (0.49%) were observed. 32.4% (12/37) of SRs could identify their external and subjective triggers. SRs patients had higher 2-year SCIT compliance than no-SRs patients ( p = 0.026). The prevalence of SRs in SCIT patients with atopic dermatitis or simple allergic asthma are no statistical significance (P = 0.111). Conclusion : the incidence of SRs in this study is within an ideal range. Through professional patient education and pre injection risk factor assessment, Compliance is still well-controlled and guaranteed although SRs occurred.